Implementasi Algoritma Apriori untuk Menentukan Pola Pembelian Konsumen (Studi Kasus : Toko SRC Nanik di Wonogiri – Jawa Tengah): Bahasa Indonesia - -, Erni Seniwati; Fahrizal Wahyu Syaiful Anam; Ninik Tri Hartanti (Politeknik Aceh, 2024)
SRC Nanik is a grocery store that sells various basic and daily necessities, such as food, drinks, personal equipment, and so on. SRC Nanik is located in Purwantoro, Wonogiri, Central Java and was founded in 2010 by Giriyanto. Every retail business must have transaction records of its operational activities, whether recorded manually in books or using a computer. However, in fact, this transaction data is rarely used by shop owners, even though the transaction records can be reprocessed to produce information that is useful for shop owners. One of them is by using data mining. Given these problems, it is necessary to utilize data to determine business strategies. The transaction data is processed using an a priori algorithm to provide new knowledge that can be utilized by retail owners. This study uses an a priori algorithm for efficient data processing, using association rules to reveal combinations of items that meet predetermined support and confidence values. Based on the a priori algorithm method, it can identify purchasing patterns that occur at SRC Nanik, with the associations formed it can be used to understand customer shopping habits and can be used to improve sales strategy.